Learning behavior-driven development with JavaScript : create powerful yet simple-to-code BDD test suites in JavaScript using the most popular tools in the community - Amodeo, Enrique (Community experience distilled., 2015)
This book is ideal for any JavaScript developer who is interested in producing well-tested code. If you have no prior experience with testing, Node.js, or any other tool, do not worry, as they will be explained from scratch.